New Actors in Employment Relations in the Periphery: Closing the Representation Gap amongst Micro and Small Enterprises - Webster, Edward; Bishoff, Christine (Relations industrielles / Industrial Relations, 2011)
This paper aims to contribute to our understanding of how the representation gap in micro and small enterprises (MSEs) in nine countries can be closed through a mapping exercise (both horizontal and vertical). The study draws on peripheral workers in MSEs predominantly from countries on the periphery of the global economy. The assumption underlying the research is that the failure of traditional industrial relations actors, especially trade unions, to respond to the representation gap has created the space and the need for new actors to fill the gap. We identify a number of dimensions in trade union responses to non-standard employment relations and focus on their awareness of the specific nature of non-standard workers’ interests and their willingness to innovate with representation models.The paper identifies four main responses by trade unions to non-standard employees. The first response is where trade unions are indifferent to workers in MSEs as they are seen as marginal and unorganizable. Secondly, there are trade unions that are very much aware of the need to revise and revitalize their representation strategies, but they respond by attempting to extend existing forms of representation. Thirdly there are those who believe that non-standard employment should be resisted. The fourth, and most interesting response, is where unions create specific kinds of representation and protection for the new forms of employment.While there were positive outcomes both individually and organizationally from this mapping exercise, as an organizational tool designed to recruit members into the union, mapping is limited. In five of the nine case studies peripheral workers were recruited into a union or worker association. The paper confirms the existence of new actors in employment relations in developing countries. In particular the emergence of NGOs and community based worker associations and co-operatives have been identified as crucial intermediaries in developing new forms of workplace organization.